Quality Improvement of Waste Tyre Pyroysis Oil by Using Cu/HMOR as a Catalyst - R. Yuwapornpanit; S. Jitkarnka (Chemical Engineering Transactions, 2014)
Metal-loaded zeolites are interesting catalysts for the improvement of the quality and quantity of waste tyre pyrolysis products. Since the catalysts exhibit multi-functions in catalysis, including hydrogenation, dehydrogenation, ring-opening, cracking, etc. that can be acquired from metal and zeolite properties. This work studied the effect of 5 wt%Cu/HMOR catalyst on waste tyre pyrolysis products. Since copper is widely used in several applications such as selective hydrogenation of undesired unsaturated hydrocarbons in a mixed-C4 stream, and sulphur removal from liquid fuels, etc. Catalytic pyrolysis of waste tyre was operated in a bench reactor. GCxGC-TOF/MS and SIMDIST-GC instruments were used to analyze the liquid products. Sulphur distribution in the pyrolysis products was determined by using an S-analyzer. As compared with the HMOR catalyst, the Cu/HMOR decreased the amount of olefins, naphthenes, poly-aromatics, and polar aromatic compounds in oils while the amounts of paraffins, di- and mono-aromatics in oils were increased because the presence of copper can promote hydrogenation, ring- opening, and cracking activities of HMOR zeolite. Furthermore, Cu/HMOR catalyst not only reduced heavy compounds in the oil but also sulphur content in the oil (reduced from 1.08 wt% to 0.907 wt% in the HMOR case), indicating that the quality of the oil as a combustion fuel was improved by using copper as a promoter of HMOR zeolite. An interesting result was that the valuable products produced in the Cu/HMOR case were benzene (1.14 wt% in oil), toluene (2.65 wt% in oil), and ethylbenzene (5.39 wt% in oil), which have never been found in the non-catalytic case or in the case when the parent HMOR was used.